Analisis Technology Acceptance Model Penerimaan Website Ilmukomputer.Com Pada Mahasiswa Teknik Informatika - Sri Hadianti; Heckel Sungkar; Resti Kartika Dewi; Siti Nurlela; Achmad Rifai; Laela Kurniawati (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2020)
Website Ilmukomputer.com is an e-Learning community that shares literature and lecture materials for free in the field of computing aka computer science and information technology in the Indonesian language. The main mission is to take part in the efforts to educate the nation's children, especially in computer science education, because the content of the website Ilmukomputer.com contains about computer science is more detailed again compared with the science of engineering faculty students get on campus.This research is done by using Technology Acceptance Model (TAM) method. This research uses 3 (three) variables, namely Perceived usefulness, Perceived Ease of Use and Attitude Toward Using. The data used are primary data obtained through questionnaire survey to students of Faculty of Informatics Engineering in Kota Bandung who has been using Ilmukomputer.com Website as a medium of information with a sample of 100 people. Data processed using SPSS software version 22.The results of this study note that the perception of benefit significantly affect the user attitude that is equal to 0.652 or 65.2%, the perception of ease of influence on user attitudes that is equal to 0.735 or 73.5%, and perceptions of usefulness, perceived ease of use significantly influence the attitude of users with the level Relationship R 0.877 = 87.7% and Rsquare 0.770 = 77%.